THE INFLUENCE OF THE USING OF VIRTUAL LAB ON THE CHEMISTRY LEARNING MOTIVATION AND ACHIEVEMENT OF GRADE XI STUDENTS OF SMA NEGERI 1 SLEMAN SEMESTER 2 ACADEMIC YEAR 2015/2016 - Marita Dean Rachma; M.Pranjoto Utomo (Jurnal Riset Pembelajaran Kimia, 2016)
This study was aimed to determine whether there is any significantdifference in motivation to learn chemistry or not before and after the using ofacid-base virtual lab, whether there is any significant increasing in motivation tolearn chemistry or not between the students who use acid-base virtual lab inpracticum activity and who do not, whether there is any significant difference inlearning achievement or not if prior knowledge is statistically controlled.This study was designed as a research experiment with one factor design,two variables, and one co-variable. One factor was in the form of learning media,two variables motivation and learning achievement, one co-variable was of priorknowledge. Samples of this research were two classes of grade XI students ofSMA Negeri 1 Sleman. One class was given a treatment of the use of virtual lab(experiment class) and one class was not (normal class). The data were collectedwith documentation technique, exercises, and inquiries. Motivations andachievements data were analyzed using same subject t-test, different subject t-test,and covariant test.The results of this research show that there is any significant difference inthe motivation of students’ before and after the using of acid-base virtual lab,there is no significant increasing in learning motivation between students’ whoused acid-base virtual lab in practicum activity with who did not, there areincreasing in achievement and motivation to learn chemistry if prior knowledge isstatistically controlled.